LICHEN SEBAGAI BIOINDIKATOR KUALITAS UDARA DI KECAMATAN JEBRES KOTA SURAKARTA - Rina Wahyu Ramadhani; Nadia Salsabila; Kistantia Elok Mumpuni (Program Pascasarjana Universitas Riau, 2022)
Surakarta is a city with polluted air due to transportation activities. Utilization of bioindicators could be one of efforts to monitor air pollution. Lichen is one of the air quality bioindicators that can be observed based on its morphological characteristics. This study aimed to determine air quality using lichen bioindicators at two stations in the Jebres sub-district, namely on UNS street and Juanda street. These two locations have different environmental characteristics and traffic density. This study is a descriptive exploratory research using purposive sampling method. The collected data were analyzed qualitatively based on the morphological characteristics of the lichen found. The results showed that nine species of lichen found in UNS street area, while five species of lichen in Juanda street area. Apparently, morphological character of lichen consisted of crustose, leprose, and foliose thallus types with bright thallus colour, larger diameter, and more individuals, whereas in Juanda street is crustose and leprosy with a duller color, smaller diameter, and fewer individuals. In fact, the vehicle density in the area of Juanda street was higher than UNS street area. As it is largerly known that the type and morphology are influenced by the environmental quality. Therefore, based on the founded lichen’s type and morphology, the area of Juanda street was likely more polluted than UNS street area. Our finding suported that lichen could be bioindicator for air quality.